Cardiac structure and function across the continuum of glucose metabolism - Tommi Grönlund; Kari Kaikkonen; M. Juhani Junttila; Olavi Ukkola; Risto Kerkelä; Heikki V. Huikuri; Mikko P. Tulppo (Physiological Reports, 2025)
Abstract Diabetes and prediabetes increase the risk of heart failure, but the relationship between glycated hemoglobin (HbA1c) and left ventricular systolic function in the general population is not known. This study aimed to investigate the relationship between HbA1c and global longitudinal strain (GLS) in nondiabetic and prediabetic subjects. A subpopulation of the Northern Finland Birth Cohort 1966 took part in a follow‐up, including extensive medical examination and echocardiography (n = 1155), at the age of 46. The final study population included 636 healthy subjects. Normal HbA1c levels were divided into sex‐specific tertiles and prediabetes, which were later pooled together. Univariate analysis after adjusted with covariates was used to compare cardiac function in HbA1c groups. HbA1c groups were defined as low (30.9 ± 1.7 mmol/mol, n = 190), medium (34.6 ± 1.0 mmol/mol, n = 189), high (37.4 ± 1.0 mmol/mol, n = 190) and prediabetes (41.0 ± 1.3 mmol/mol, n = 67) groups. Subjects with abnormal absolute GLS (<18) comprised 7.4%, 12.7%, 21.1%, and 17.9% (main effect p < 0.01) of low, medium, high HbA1c and prediabetes groups, respectively. HbA1c was not associated with any cardiac structure variables. High normal HbA1c levels and prediabetes are associated with reduced myocardial contractility in a healthy middle‐aged population, potentially predicting the development of heart failure.